Pengaruh Kualitas Produk, Pelayanan, dan Kepercayaan Nasabah terhadap Keputusan Pembelian Produk Asuransi di PT AIA Financial - Achmad Faqih; Yugi Setyarko (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine and analyze the influence of product quality, service quality, and customer trust on insurance product purchasing decisions at PT AIA Financial at BCA KCP Raden Saleh, Central Jakarta. The background of this study is based on the importance of understanding the factors that influence purchasing decisions, especially in the insurance industry, which is intangible and highly dependent on customer perception and trust. This study uses primary data collected through questionnaires distributed to 47 respondents, namely PT AIA Financial customers who have purchased insurance products at the research location. The research instrument is compiled based on variable indicators whose validity and reliability have been tested. The data analysis method used is a quantitative method with a multiple linear regression analysis approach through the assistance of SPSS software version 26. Product quality is measured through the dimensions of performance, durability, suitability, and features; service quality is assessed from the aspects of reliability, responsiveness, assurance, empathy, and physical evidence; while customer trust is seen from the reliability of the company, agent integrity, and clarity of information. The results of the study indicate that product quality, service quality, and customer trust partially and simultaneously have a positive and significant effect on insurance product purchasing decisions. This means that the higher the quality of the products and services provided, and the greater the customer trust, the higher the customer's tendency to purchase PT AIA Financial's insurance products. This finding implies that the company needs to continuously maintain and improve its product quality, provide excellent service, and build and maintain customer trust through transparent communication, clear product education, and a commitment to service promises. This way, long-term relationships with customers can be maintained and customer loyalty can be enhanced.